2020
DOI: 10.1111/clr.13583
|View full text |Cite
|
Sign up to set email alerts
|

Facial alveolar bone alterations and gray value changes based on cone beam computed tomography around maxillary anterior implants: A clinical retrospective study of 1–3 years

Abstract: Objectives:The purpose of this cone beam computed tomography (CBCT) study was to describe facial alveolar bone alterations and gray value (GV) changes around implants in aesthetic anterior maxilla with simultaneous guided bone regeneration (GBR) and to investigate potential influence of factors related to vertical alveolar bone stability, such as particle sizes of the deproteinized bovine bone mineral (DBBM) used. Materials and Methods:A retrospective study design was adopted. Four facio-palatal cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Further, consistent with previous studies, we found that a higher number of graft contact walls effectively reduces the risk of implant apical non-coverage (Lombardi et al, 2017;Zhou et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, consistent with previous studies, we found that a higher number of graft contact walls effectively reduces the risk of implant apical non-coverage (Lombardi et al, 2017;Zhou et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Further, consistent with previous studies, we found that a higher number of graft contact walls effectively reduces the risk of implant apical non‐coverage (Lombardi et al., 2017; Zhou et al., 2020). Moreover, our findings highlight that a larger distal angle inversely affects the risk of implant apical non‐coverage.…”
Section: Discussionsupporting
confidence: 92%
“…The assessment of optical density in CBCT (cone beam-computed tomography) is not easy due to the impossibility of using the Hounsfield scale. The assessment of alveolar ridge dimensions [ 19 ], on the other hand, does not mention the presence of living bone [ 20 ]. Furthermore, the presence of living hard tissue allows for long-term clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the cross-sectional images were rotated to align T1 and T2. Thirdly, the positions of the adjacent teeth and anatomical structures were referenced to superimpose the T0 image (Zhou et al, 2020).…”
Section: Radiographic Measurementmentioning
confidence: 99%